2021
DOI: 10.12911/22998993/142274
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Implications and Source Apportionment of Heavy Metal and Hydrocarbon Contaminants in the Soil of a Poorly Crude Oil Remediated Site in Nigeria: A Case of Ikot Ada Udo Community

Abstract: The ecological risk and source apportionment of heavy metals and hydrocarbons in soil from the study site was carried out. Composite soil samples (n = 48) were collected from 3 sampling points (SP 1, SP 2, SP 3) within the site at 50, 200, and 500 meters, respectively, from the oil well and from a control site (Ibagwa, Abak) at 10,000 meters from the study site, using a hand-held auger. The samples were analyzed for heavy metals using inductively coupled plasma atomic emission spectrometry (ICP-AES, Yobin Yvon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…4), Fe (798.32%) had the highest Coefficient of variation (CV), followed by Cd (747.33%), and finally Cd (95.65%). For the apportionment of heavy metal sources, famous researchers from around the world have successfully employed statistical analysis CV (Akaninyene et al, 2021;Wang et al, 2021;Eyankware et al, 2022). With the exception of Mn, Pb, Zn, Cr, and As, which ranged from 26.83%, 27.06%, 2.642%, 26.72%, and 26.77%, respectively, the conducted study showed that the CV of Cu, Fe, Cd, and Fe pollutants were above 60%.…”
Section: Statistical Analysis Results From Heavy Metalsmentioning
confidence: 99%
See 2 more Smart Citations
“…4), Fe (798.32%) had the highest Coefficient of variation (CV), followed by Cd (747.33%), and finally Cd (95.65%). For the apportionment of heavy metal sources, famous researchers from around the world have successfully employed statistical analysis CV (Akaninyene et al, 2021;Wang et al, 2021;Eyankware et al, 2022). With the exception of Mn, Pb, Zn, Cr, and As, which ranged from 26.83%, 27.06%, 2.642%, 26.72%, and 26.77%, respectively, the conducted study showed that the CV of Cu, Fe, Cd, and Fe pollutants were above 60%.…”
Section: Statistical Analysis Results From Heavy Metalsmentioning
confidence: 99%
“…The region still struggles with oil pollution and contamination, which has a big impact on people despite having a rich, diverse ecology and wildlife (Amnesty International Nigeria, 2009;Ordinioha and Brisibe, 2013). The Gulf of Mexico in 2010, Canadian marine waters, and Prince Williams Sound, Alaska, all reportedly experienced oil spillage occurrences (Akaninyene et al, 2021). As about 13 million tonnes of crude oil have flowed into the Niger Delta ecosystem since crude oil was discovered there (Orisakwe, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sources of these metals such as mercury, cadmium, copper, and zinc vary and they include solid wastes [ 20 , 21 ] as well as agriculture and aquaculture [ 11 , 35 ]. As these metals accumulate in the environment, at certain critical levels, they trigger co-selection mechanism with antibiotics resistance [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The limits of detections were 0.052 (Pb), 0.018 (Cd), 0.015 (Mn), 0.025 (Ni), 1.790 (Zn), 0.079 mg/kg (Cr), 0.02 mg/kg (Fe) and 0.01 mg/kg (Co). Concentrations of heavy metals were expressed in mg/kg dry weight [ 35 ].…”
Section: Methodsmentioning
confidence: 99%